Engineering performance of cement mortar with partial replacement of date palm leaf ash and addition of date palm fibers - Hasan Omar Ali Alhaddad (2023)
The focus for this study is to investigate the roles of date palm leaf ash and fibers at enhancing the engineering behavior of mortar. Date palm trees are widely grown in the Middle East countries. Date palm trees can pose a problem to the environment as it decays and the resultant organic remnants of the trees are acidic and contribute to environmental pollution. Furthermore, date palm fibers are known to have the reinforcing property that can improve the tensile strength of mortar. On the other hand, date palm leaves can be incinerated to ash in order to be added as pozzolanic additive of mortar for long term strength accumulation. The trial mix designs were varied with date palm leaf ash of 1% to 10% as partial substitute of cement and date palm fibers of 1% to 5% as partial substitute of silica sand. Experimental works were carried out in order to evaluate the mechanical properties of the mortars enhanced with date palm leaf ash and fibers. The tests include compression, flexural, water absorption and ultrasonic pulse velocity. Besides, scanning electron microscopic (SEM) and energy dispersive X-ray (EDX) tests were used to characterize the microstructure ad chemical properties of the mortar mixes. As the major finding of the study, it was realized that the optimal mix ratio of the improved mortars were noticed to have 4% date palm leaf ash as partial cement substitute and 2% date palm fibers as partial silica sand substitute. The cement mortars were found to have an optimal water to cement ratio of 0.65 in term of 28-day compressive strength. Based on the optimal mix design, it was tested that the improved mortars had an average 28-day compressive strength of 31.3 MPa, an average density of 1909 kg m-3,an average flexural strength of 3.22 MPa, an average ultrasonic pulse velocity of 4048 m s-1 and an average water absorption of 2.96%. There were significant improvement in the mechanical properties of the improved mortars as compared to those of the cement mortars. Better packing efficiency could be observed in the microstructure of the improved mortar sample when compared to that of the cement mortar sample. This was attributed to the combined action of both the date palm leaf ash and fibers at clogging the pore spaces and increased the ductility of the improved mortars. The study outcomes proved that both date palm leaf ash and fibers can cause pozzolanic activity and reinforcing effecton the improved mortars.